Prevalence of Erectile Dysfunction Among Men with Type 2 Diabetes Mellitus in Indonesia: An Observational Study - Primanda, Yanuar; Nugroho, Taufik Wiyoga; Lokeesan, Vignesvararajah (Universitas Muhammadiyah Yogyakarta, 2023)
Background: Diabetes mellitus (DM) is a chronic metabolic disorder that can lead to multiple long-term complications in the human body including erectile dysfunction (ED). ED is a condition that commonly affects men and may reduce their quality of life. However, ED amongst men with type 2 DM (T2DM) has rarely been assessed and addressed by nurses who have an essential role in providing holistic patient care.Objective: This study aimed to describe ED among men with T2DM based on their demographic characteristics and health profiles.Methods: This was a descriptive study with a cross-sectional approach of 32 male respondents who were selected through convenience sampling in the outpatient department of PKU Muhammadiyah Hospital Yogyakarta, Indonesia. The data was collected by using the erectile function’s domain of Indonesian version of International Index of Erectile Function (IIEF). Descriptive statistics were used to present this study’s findings.Results: The results showed that 62.5% of the participants had uncontrolled blood glucose levels with an average random blood glucose of 207.75 ± 77.21 mg/dl. Only four respondents (12.5%) had received sexual counselling. Twenty-nine respondents (90,6%) had ED which were categorized into mild (17.2%), mild to moderate (6.9%), moderate (24.1%) and severe (51.7%).Conclusion: ED levels varied across age, duration of T2DM, random blood glucose levels, previous history of smoking, current smoking status, sexual counselling experience, complications, and occupation levels. Severe ED was common amongst men with T2DM in this study. Nurses should assess patient’s sexual function regularly and identify the effects of ED in men with T2DM. Early detection of ED could allow nurses to plan adequate intervention and health education to provide better outcomes for men with T2DM.